Analisa Daya Tahan Kardiovaskuler Atlet Lari Jarak Jauh dengan Pendekatan Latihan Overhead Extension dan Continuous Run - Setiawan, Donny (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aimed to measure the comparative effectiveness of continuous running and overhead extensions in improving cardiovascular endurance in long-distance runners at the JAS Athletic Club. Using a two-group pretest-posttest experimental design with a sample of 20 athletes, the study found that both exercises increased cardiovascular endurance (VO₂max). However, the effect of continuous running was significantly greater. These findings indicate that continuous running is superior for aerobic endurance, while overhead extensions are more suitable as a supplementary exercise for muscle strength.